Acupuncture Care for Lumbar Pain Case Due to Lumbosacral Instability at Griya Sehat BSA Holistik Pontianak - Sutiyoso, Seneng; Wulandari, Mayang; Candra , Leny (Jurnal Indonesia Sosial Sains, 2025)
Supervisor II, dr. Leny Candra, A. Md. Akp., MM Lumbar pain due to Lumbosacral Instability is one of the musculoskeletal complaints that is often found. Acupuncture as a complementary therapy has been used to reduce pain in cases of low back pain. This study is to determine the benefits of Acupuncture Care for Clients with Low Back Pain Due to Lumbosacral Instability at Griya Sehat BSA Holistik Pontianak comprehensively. The subject of the study was a 43-year-old male client who experienced lumbar pain and underwent acupuncture therapy at Griya Sehat BSA Holistik Pontianak. The research design uses a qualitative approach of the case study type. In-depth data collection is carried out using instruments in the form of Client Data Sheets. The data was processed based on Observation (Wang), Hearing and Smell (Wen), Interview (Wen), and Touch (Qie), hence the diagnosis of client syndrome Cold Moist Pathogen Attacking the Taiyang Meridians of the Bladder Leg. The intervention was carried out by needle insertion at acupuncture points according to the syndrome from the results of diangnose six meetings with an interval of three days. The results showed a significant decrease in the level of lumbar pain in clients after receiving acupuncture care. Pain complaints disappear, movement reflexes increase. In order for clients to stay healthy, it is recommended to avoid lifting heavy objects, exercise regularly, air conditioning or fans do not be directed at the body directly, drink enough water, and sunbathe every morning.